The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.2967/jnumed.111.089482
|View full text |Cite
|
Sign up to set email alerts
|

Tumor 3′-Deoxy-3′-18F-Fluorothymidine (18F-FLT) Uptake by PET Correlates with Thymidine Kinase 1 Expression: Static and Kinetic Analysis of 18F-FLT PET Studies in Lung Tumors

Abstract: The absence of observable correlations of the imaging parameters with TK1 activity suggests that (18)F-FLT uptake and retention within cells may be complicated by a variety of still undetermined factors in addition to TK1 enzymatic activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 27 publications
(25 reference statements)
2
28
1
Order By: Relevance
“…3). Competition of endogenous thymidine and 18 F-FLT for binding to nucleoside transporters or the catalytic site of TK1 has been described before (22,32). Indeed, we showed a significant negative correlation of tumor thymidine level with 18 F-FLT uptake (Fig.…”
Section: Discussionsupporting
confidence: 75%
“…3). Competition of endogenous thymidine and 18 F-FLT for binding to nucleoside transporters or the catalytic site of TK1 has been described before (22,32). Indeed, we showed a significant negative correlation of tumor thymidine level with 18 F-FLT uptake (Fig.…”
Section: Discussionsupporting
confidence: 75%
“…Keen et al reported a strong correlation between 18 F-FLT uptake, tk-1 expression, and Ki-67 expression in a human xenograft carcinoma model (29), but the relationship between tk-1 and Ki-67 expression is not evident in every carcinoma model, as Ki-67 represents a somewhat larger amount of the cell cycle than tk-1 (29). Brockenbrough et al recently suggested that the 18 F-FLT uptake may also be influenced by factors besides tk-1 activity, including competition with endogenous thymidine, transport via nucleoside transporters, the degradative metabolism of phosphorylated metabolites, and the rate of DNA repair (37). Additionally, changes in perfusion rate, vascular permeability, and the activity of nucleoside transporters may alter 18 F-FLT uptake independently of cell proliferation (31).…”
Section: Discussionmentioning
confidence: 99%
“…In a cohort of 25 suspected lung cancer patients, 18 F-FLT PET images were performed before surgical resection and compared with expression of Ki-67 and TK1 determined by immunohistochemical staining (67). TK1 enzymatic activity was also determined in extracts from flashfrozen samples of the tumors.…”
Section: Lung Cancermentioning
confidence: 99%